Implementation of the state policy on children in Tula oblast - Shaidenko Nadezhda Anatolievna; Orekhova Elena Yakovlevna; Svetlana Nikolaevna Kipurova (SHS Web of Conferences, 2021)
The profound and comprehensive crisis faced by the Russian Federation in the 1990s severely affected families and children. With the advent of the new millennium, however, funding for all aspects regarding family and children increased and the role and responsibilities of state agencies were enshrined in legislation. The change in interpersonal relations, women’s employment, and the focus on reducing the number of orphanages through various forms of foster care support the need for new ideologies and measures to support families and orphans and children left without parental care. This supports the importance of analyzing the regional policy in the sphere of family and orphans based on the state legislation on the one hand and the regional normative legal documents stemming from this experience on the other. The study uses the methods of specific sociological techniques: surveying, content analysis of the regional press on the problems of the social sphere, and analysis of legislative and regulatory documents and statistical data. The article identifies the problems present in education in the studied region, as well as significant positive changes primarily in rehabilitation work with parents deprived of parental rights to return children to their families. The authors propose a strategy for early prevention of family dysfunction based on increased cooperation between all regional subjects of upbringing. Forms of socio-pedagogical support for families with foster children are highlighted separately. The main reason for the continuing problems in the region is the lack of activity on the part of most social systems having the potential of pedagogical impact. In terms of future perspectives, the authors indicate the need to develop educational and developmental multivariate programs focused on the development of competent parenthood in the region.